EXTREME CEREBRAL MALFORMATION – CLINICAL AND ETHICAL ISSUES BASED ON A CASE - Florin Brezan; Ioana Codreanu; Rodica Cretu; Lucica Ghita; Mirela Ritivoiu; Diana Goran; Ioana Alina Anca (Romanian Journal of Pediatrics, 2014)
Hydranencephaly represents one of the most rare cerebral malformations, with poor prognosis and negative impact on both family and society. Usually the patients remain in a permanent vegetative state and require unlimited medical care. Although the majority of affected babies die in utero or in the fi rst days-months of life there have been cases in literature with prolonged survival, for 20 (1), 22 (2) and 32 (3) years. Therapeutically, the medical care provided are purely palliative and oriented to supporting vital function. Conclusions. Hydranencephaly is a rare brain malformation with poor prognosis, life expectancy and quality of life. Diagnosis imposes a number of ethical issues. The importance resides in the fact that prenatal detection represents an indication for therapeutic abortion. Another ethical issue raised is represented by medical care provided, which is exclusively palliative. Both surgical and novel therapeutic methods described by the literature, like endoscopic coagulation of choroid plexes, do not infl uence the neurological status and the neuropsychomotordevelopment (4). All this data should be clearly explained to parents and legal tutors for not raising any false hopes regarding the evolution.